Anaplastic large cell lymphoma, ALK-positive and anaplastic large cell lymphoma ALK-negative (Hematology Meeting Reports, 2009)
In the 3rd edition of the WHO Classification of Hematopoietic Neoplasms, anaplastic lymphoma kinase-positive (ALK+) and anaplastic lymphoma kinase-negative (ALK–) anaplastic large cell lymphoma (ALCL) were considered as a single disease entity and defined as lymphomas consisting of lymphoid cells that were usually large with abundant cytoplasm and pleomorphic, often horseshoe- shaped nuclei.1 The cells are CD30-positive2 and most cases express cytotoxic granule-associated proteins3,4 and EMA.5 It became clear that while ALCL expressing ALK constituted a relatively homogeneous entity, cases with similar morphology and phenotype but lacking ALK expression were much more heterogeneous. In the 4th WHO classification, ALCL, ALK+ is a distinct entity and ALCL cases without ALK expression are a provisional entity.6 ALK+ ALCL are associated with a chromosomal abnormality, the t(2;5)(p23;q35), that fuses part of the nucleophosmin (NPM) gene on chromosome 5q35 to a portion of the ALK (anaplastic lymphoma kinase) receptor tyrosine kinase gene on chromosome 2p23, resulting in the expression of a unique chimeric NPM-ALK protein.7,8 Besides the t(2;5), at least eleven variant translocations involving ALK gene at p23 have been recognized. All result in upregulation of ALK fusion protein. Primary systemic anaplastic large cell lymphoma, both ALK+ and ALK–, must be distinguished from ALCL of primary cutaneous type and from other subtypes of T or B-cell lymphoma with anaplastic features and/or CD30 expression (Jaffe 2001).